Oxidative addition across Sb–H and Sb–Sb bonds by an osmium carbonyl cluster : trapping the intermediate - Li, Ying-Zhou (2014)
The cluster Os3(CO)11(NCCH3) oxidatively adds across the Sb–H bond in SbPh2H to afford the clusters Os3(CO)11(H)(μ-SbPh2) and Os3(CO)11(μ-H)(μ-SbPh2)Os3(CO)11. Similarly, its reaction with Sb2Ph4 afforded Os3(CO)11(μ-SbPh2)2Os3(CO)11 as the major product. In both cases, the intermediate from the oxidative addition reaction was trapped as a W(CO)5 adduct.